2021 International Conference on Information Networking (ICOIN) 2021
DOI: 10.1109/icoin50884.2021.9333913
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Algorithm for Detection of False Data Injection Attack in Power System

Abstract: Electric grids are becoming smart due to the integration of Information and Communication Technology (ICT) with the traditional grid. However, it can also attract various kinds of Cyber-attacks to the grid infrastructure. The False Data Injection Attack (FDIA) is one of the lethal and most occurring attacks possible in both the physical and cyber part of the smart grid. This paper proposed an approach by applying machine learning algorithms to detect FDIAs in the power system. Several feature selection techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…• Energy Sector: As we discussed earlier in this article machine learning has been heavily used in the energy sector. In [126] a comparative study using random forest, support vector, naive Bayes, decision tree, and AdaBoost was performed to predict false data injection attacks in power systems. The experiment performed showed random forest yielded the most accurate results with and without feature selection and is very effective in such types of problems.…”
Section: Applications Of Machine Learningmentioning
confidence: 99%
“…• Energy Sector: As we discussed earlier in this article machine learning has been heavily used in the energy sector. In [126] a comparative study using random forest, support vector, naive Bayes, decision tree, and AdaBoost was performed to predict false data injection attacks in power systems. The experiment performed showed random forest yielded the most accurate results with and without feature selection and is very effective in such types of problems.…”
Section: Applications Of Machine Learningmentioning
confidence: 99%
“…The authors in [67] used minority oversampling and feature selection to improve the detection of FCIAs on power systems using machine learning. The authors in [68] showed that the performance of various ML models to detect FCIAs is dependent on pre-processing and feature selection. Various ML models analyzed include Random Forest (RF), Support Vector Machine (SVM), Naive Bayes (NB), etc.…”
Section: A Artificial Intelligence-based Techniquesmentioning
confidence: 99%
“…Attacks in this category include replay and false injection. Studies in [56–59] have investigated these attacks and suggested prevention algorithms. These include cryptography, message verification, time stamp verification, and machine learning.…”
Section: Cyber Attacks In Cavsmentioning
confidence: 99%